2013
DOI: 10.4172/2155-6156.s13-008
|View full text |Cite
|
Sign up to set email alerts
|

Role of Adipose Tissue in Metabolic System Disorders

Abstract: Based on the location of AT in the body, it is divided into two forms; apple or pear shapes. In apple-shape adiposity (visceral or central obesity), fat pads (fat depot) accumulate mostly in the abdominal cavity and around intra-abdominal organs. Central obesity increases the risk for metabolic problems. However, in pear-shape adiposity (peripheral obesity), extra fat is stored subcutaneously and around hips, thighs and AbstractThe pathogenesis of obesity-induced metabolic syndrome is due to the dysfunction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 99 publications
(147 reference statements)
0
7
0
Order By: Relevance
“…Mammary adipose tissue in the tumor microenvironment displays persistent inflammation and harbors crown like structures, which are well-known inflammatory foci (62). We therefore propose that mammary adipose tissue displays local inflammation (as a result of DIO) similar to what is observed in visceral adipose tissue of obese individuals (52,63) and as a result may play a significant role in obesity-induced breast cancer treatment resistance. It is speculated that treatment resistance may be the result of inflammation found in the mammary adipose tissue as a result of the HFD and doxorubicin treatment.…”
Section: Inflammatory Markers: Diet-induced Obesity Induces Systemic mentioning
confidence: 74%
“…Mammary adipose tissue in the tumor microenvironment displays persistent inflammation and harbors crown like structures, which are well-known inflammatory foci (62). We therefore propose that mammary adipose tissue displays local inflammation (as a result of DIO) similar to what is observed in visceral adipose tissue of obese individuals (52,63) and as a result may play a significant role in obesity-induced breast cancer treatment resistance. It is speculated that treatment resistance may be the result of inflammation found in the mammary adipose tissue as a result of the HFD and doxorubicin treatment.…”
Section: Inflammatory Markers: Diet-induced Obesity Induces Systemic mentioning
confidence: 74%
“…After many years of research, studies have shown that the expression of uncoupling protein 1 (UCP1) in response to cold stress, or food intake resulting in regulation of energy balance (increased glucose and free fatty acid oxidation) leads to the generation of heat and serves to protect an organism from hypothermia (Algire et al, 2013;Roman et al, 2015;Sidossis and Kajimura, 2015). BAT is characterized by small lipid droplets (LDs) and microstructurally high number of mitochondria (Kiefer et al, 2012;Rezaee, 2013). Storage of energy in the form of triglycerides (TGs) in LDs is accessible for rapid hydrolysis and oxidation of fatty acids (FAs) (Rezaee, 2013;Warner and Mittag, 2016).…”
Section: White and Brown Adipose Tissuementioning
confidence: 99%
“…BAT is characterized by small lipid droplets (LDs) and microstructurally high number of mitochondria (Kiefer et al, 2012;Rezaee, 2013). Storage of energy in the form of triglycerides (TGs) in LDs is accessible for rapid hydrolysis and oxidation of fatty acids (FAs) (Rezaee, 2013;Warner and Mittag, 2016). BAT is derived from precursor cells, which share the same lineage as skeletal muscle cells and are positive for Myf5 (Zafrir, 2013;Giralt and Villarroya, 2016).…”
Section: White and Brown Adipose Tissuementioning
confidence: 99%
“…Since the discovery of leptin, 21 years ago (1), the adipose tissue was the focus of several functional studies, in such a way that nowadays it could be considered as a potent endocrine and immune organ (25). This feature is due to the peculiarity of the different cells that form this tissue: adipocytes, preadipocytes, endothelial cells, fibroblasts, and numerous immune cells including macrophages, B cells, T cells, and neutrophils mainly.…”
Section: Introductionmentioning
confidence: 99%